213P Sensitivity to change of the motor function measure (MFM) in myotonic dystrophy type 1 - Ribault, S.; Rippert, P.; Bassez, G.; Duong, T.; Vuilllerot, C. (Neuromuscular disorders : NMD, 2024)
Myotonic dystrophy type 1 (DM1) is a hereditary multisystemic disease characterized by progressive muscle wasting, heart conduction abnormalities, early-onset cataract, and endocrinological disorders. It is caused by a non-coding CTG repeat expansion in the DMPK gene. With new therapeutic advancements and ongoing clinical trials focusing on siRNA, antisense oligonucleotides or gene therapy, there is an imperative to identify a suitable clinical outcome to assess motor function in DM1. The Motor Function Measure is a 3-dimensional quantitative scale (D1: standing/transfers, D2: Proximal/axial, D3: Distal) designed to monitor motor function in patients with neuromuscular diseases encompassing the spectrum of the disease regardless disease severity or functional level. This is a multicentric retrospective review of adults and children with a genetic diagnosis of DM1. Included subject were male or female DM1 patients with the availability of at least 2 MFM32 scores at 1 year. MFM32’s mean slope of change and standard response mean (SRM) were calculated. 343 subjects were included. At the first MFM mean age was 36.3 years (+/- 16.1, min: 6.1yo; max: 71.8yo), and mean MFM32 scores were 69.1%+/-25.1, 91.9%+/-9.1, 90.8.1%+/-8.4, and 82.4%+/-13.8 for D1, D2, D3 and Total score respectively. Average time between first and last assessments was 5.1 years (+/- 3.6, min: 1 y; max: 15.9yo). MFM32’s yearly mean slope of change was -2.25% (+/-3.86) for D1, -1.09% (+/-3.50) for D2, -0.54% (+/-2.95) for D3, -1.44 (+/-2.46) for total score. SRM was -0.58 for D1, -0.31 for D2, -0.18 for D3, -0.59 for total score. Understanding the change over time in a natural history cohort is important to understand the impact of change against a changing disease landscape. We showed MFM32’s responsiveness to change most relevant in the standing and transfer domain (D1) and MFM total score than the more proximal or distal domains.